PARENTS ROLE IN EDUCATION PROCESS AND THEIR RIGHTS, DUTIES IN COOPERATION WITH THE EDUCATION INSTITUTION - Erdmanis, Rihards (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Latvia’s educational policymakers already in 2006 pointed out that one of the main obstacles to raising public awareness about the development of education is poor teacher training for working with parents. It means that a full understanding of the educational process by parents and teachers is unthinkable without cooperation. Respectively, cooperation with educational staff, pupils, parents and family, employers, local governments and state institutions, public organizations and society are pointed out as a fundamental principle of education development policy. Alongside with the other equally important basic principles - systemicity, succession, sustainability, accessibility and coordination. In Great Britain, executive representatives recommend actively incorporating parents into educational policies and practices. The inclusion of parents in teaching-related activities alongside prepared teachers has proved to be a useful factor in improving the attendance of school, the quality of teaching and social cohesion. The author thinks that it is necessary to find out the role of parents in the education process both in pedagogy and in jurisprudence. In Latvia, there are no researches done about this topic. The Education Law of the Republic of Latvia defines both the rights and responsibilities of parents. So, it means that it is important to look closer to these rights and responsibilities.